ANALISIS HUKUM PELANGGARAN HAK CIPTA PENGGUNA APLIKASI TIKTOK DITINJAU MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Nabhila Nasution (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2021)
this TikTok application has a feature of uploading songs using songs from the application's users, which sometimes users do not allow songs uploaded to the application. The existence of taking songs without permission and then changing the time and sound effects on the sound pieces in the application indicates that a work of the song has made changes from the version of the song. The type of research used in completing the thesis is normative juridical research, namely an effort to study the rule of law as it writes. Data collection techniques are carried out through library research and field research, obtained through document studies, and the collection of TikTok videos that violate copyright. The study results indicate that the identification of copyright infringement by users of the TikTok application according to Law Number 28 of 2014 concerning Copyright is a violation of moral rights and economic rights. It is recommended to concerning the use of social media, especially the TikTok application, users of the TikTok application must pay more attention to the legal provisions in the field of Copyright in Indonesia and the terms of service for the TikTok application because, in principle, a violation of the use of the TikTok application has the potential to violate the moral rights and economic rights of the Creator/Right Holder. Copyright in the application can be sued for criminal or civil compensation as regulated in Law Number 28 of 2014 concerning Copyright.